2007
DOI: 10.2166/wst.2007.802
|View full text |Cite
|
Sign up to set email alerts
|

N-nitrosodimethylamine formation during treatment with strong oxidants of dimethylamine containing water

Abstract: The aim of the paper is the evaluation of the possibility of NDMA formation, as a result of strong oxidants reacting with DMA. Summarized results of investigations on N-nitrosodimethylamine formation as a result of dimethylamine reactions with chlorine dioxide, ozone and hydrogen peroxide are presented. Preliminary results of experiments on NDMA formation as a result of DMA reactions with permanganate are also shown. The experiments on dimethylamine reactions with chlorine dioxide, hydrogen peroxide and perman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…The general belief that oxidation decreases nitrosamine formation potential is based on the results of two papers by Lee et al [93,94], where several NDMA suspected precursors (organic compounds with dimethylamine-or trimethylamine groups) were oxidized with relatively high doses of oxidants (ozone, chlorine dioxide, ferrate and hydroxyl radicals) and then reacted with chloramine. However, there are several reports that state that oxidation of DMA may lead to the formation of NDMA [41,95,96], particularly at a higher pH. Zhao et al [39] have also shown that raw water oxidation with chlorine dioxide or ozone may increase NDMA content in treated waters.…”
Section: Removal Of Nitrosamine Precursors By Water Treatment Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…The general belief that oxidation decreases nitrosamine formation potential is based on the results of two papers by Lee et al [93,94], where several NDMA suspected precursors (organic compounds with dimethylamine-or trimethylamine groups) were oxidized with relatively high doses of oxidants (ozone, chlorine dioxide, ferrate and hydroxyl radicals) and then reacted with chloramine. However, there are several reports that state that oxidation of DMA may lead to the formation of NDMA [41,95,96], particularly at a higher pH. Zhao et al [39] have also shown that raw water oxidation with chlorine dioxide or ozone may increase NDMA content in treated waters.…”
Section: Removal Of Nitrosamine Precursors By Water Treatment Processesmentioning
confidence: 99%
“…Chlorination and chloramination are the main sources of NDMA in wastewaters and drinking waters. However, there have been several reports of NDMA formation upon the application of other strong oxidants, such as ozone, chlorine dioxide, KMnO 4 or ferrate (VI) [16,39,41,42,[87][88][89]95,96]. In general, when oxidants are in contact with dimethylamine, part of the DMA is oxidized to nitrites and nitrates (formaldehyde and formic acids are also commonly detected).…”
Section: Mechanisms Of Ndma Formationmentioning
confidence: 99%
“…Several studies have shown that other oxidants including ozone (O 3 ), chlorine dioxide (ClO 2 ) and permanganate (23)(24)(25)(26)(27)(28)(29) can oxidize amines to produce low levels of nitrosamines. Andrzejewski et al (24,27) linked nitrosamine formation during ozonation to the formaldehyde-catalyzed nitrosation since formaldehyde is a common product of ozonation.…”
Section: Background Nitrosamine Formation Chemistrymentioning
confidence: 99%
“…Several studies have shown that other oxidants including ozone (O 3 ), chlorine dioxide (ClO 2 ) and permanganate (23)(24)(25)(26)(27)(28)(29) can oxidize amines to produce low levels of nitrosamines. Andrzejewski et al (24,27) linked nitrosamine formation during ozonation to the formaldehyde-catalyzed nitrosation since formaldehyde is a common product of ozonation. In contrast, Yang et al (30) proposed two other pathways: (i) secondary amine precursors reacting with hydroxylamine to form unsymmetrical dialkylhydrazine intermediates, which are further oxidized to their relevant nitrosamines; and (ii) a nitrosation pathway in which N 2 O 4 acts as the nitrosating reagent, to be responsible.…”
Section: Background Nitrosamine Formation Chemistrymentioning
confidence: 99%
“…Measurement of low concentrations of NDMA in different water matrices can be achieved by using highly sensitive and selective instrumental methods such as GC-MS/MS (Mitch and Sedlak 2002;Schmidt and Brauch 2008;Hu et al 2008;Andrzejewski and Nawrocki 2007;Planas et al 2008;Charrois et al 2007;Grebel et al 2006;Cheng et al 2006;Charrois et al 2004;Mitch et al 2003b;Taguchi et al 1994;Yoon et al 2011) and LC-MS/MS Ripolles et al 2011;Wang et al 2010;Kosaka et al 2009;Plumlee et al 2008;Krauss and Hollender 2008;Kodamatani et al 2009;Zhao et al 2006). However, the measurement of low concentrations of NDMA not only depends on the analytical detection limit of the LC or GC employed but also on the techniques (i.e., liquidliquid extraction (LLE) or solid-phase extraction (SPE)) that are used for the recovery and concentration of NDMA from the samples and for the elimination of matrix effects.…”
mentioning
confidence: 99%